ANALISIS KUALITAS PELAYANAN PEJABAT PENGELOLA INFORMASI DAN DOKUMENTASI SEKRETARIAT DAERAH KOTA PALU - Nipo, Firman H. (Katalogis, 2016)
This research aims at identifying and analyzing the Service Quality of Information and Documentation Officers.This is a qualitative research. The informants of this research are Information and Documentation Officers of Regional Secretariat of Palu and the people represented by the media were determined by purposive sampling technique. The techniques of the data collection wereÂ observations, interviews, and documentations, while the data were analized by using data reduction, data grouping , interpretation of the data meaning, andÂ conclusions draw. The results show that the services ofÂ the officers are qualified enough despite the reliability, responsiveness, assurance, and empathy show good results, but the tangible aspect in terms of physical facilities equipment used is not adequate, the number of computers is limited, narrow room and the absence of a monitor in front of the room.